2017
DOI: 10.1007/s11571-017-9460-2
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of stress: new treatment alternatives

Abstract: Complaints of stress are common in modern life. Psychological stress is a major cause of lifestyle-related issues, contributing to poor quality of life. Chronic stress impedes brain function, causing impairment of many executive functions, including working memory, decision making and attentional control. The current study sought to describe newly developed stress mitigation techniques, and their influence on autonomic and endocrine functions. The literature search revealed that the most frequently studied tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 117 publications
0
36
0
2
Order By: Relevance
“…Especially the neurobiology of emotions (variable E) has created a neuro-psychological subdiscipline of its own: affective neuroscience. Also problem intensity (P) is related to the experience of stress and all neural and neuroendocrine mechanisms of stress regulation (Subhani et al 2018 ).…”
Section: Neural Correlates Of the Phenomenological Modelmentioning
confidence: 99%
“…Especially the neurobiology of emotions (variable E) has created a neuro-psychological subdiscipline of its own: affective neuroscience. Also problem intensity (P) is related to the experience of stress and all neural and neuroendocrine mechanisms of stress regulation (Subhani et al 2018 ).…”
Section: Neural Correlates Of the Phenomenological Modelmentioning
confidence: 99%
“…The modulated synapses in turn affect the neural responses. This feedback coupling between global network dynamics and local neuronal circuits is an important operating mode of the brain 31 and is closely related to the mechanisms of learning and memory 32,33 . However, the neuronal electric activities generated by the transmembrane flow of ions not only modulate the synaptic connection but also inevitably produce a time-varying electric field as well as a magnetic field, according to Maxwell’s theory of electromagnetic induction 3436 .…”
Section: Introductionmentioning
confidence: 99%
“…Stress reduction has become a key focus in research area owing to the increasingly demanding nature of modern lifestyles. New physiologic measures have been used to identify stress, and recent related research has paved the way for new methods in objective stress treatment (Subhani et al 2018). In a metaanalysis that evaluated the relationship between migraine and depression, it was reported that depression was approximately twice as common in migraineurs than in those without headache.…”
Section: Introductionmentioning
confidence: 99%